The influence of constructional parameters on stiffened plates sound radiation - IWANIEC, M. (Archives of Acoustics, 2005)
This work concerns the method of the plate parameter selection and the choice of the stiffening set, assuming the minimization or maximization of the energy stored or radiated by a stiffened plate as a criterion. The energy balance equations based on the SEA method were used in order to quickly evaluate the energy flow as a function of chosen constructional parameters. Calculations of mechano-acoustic energy flow were performed in AutoSEA and Matlab environment.